How Bilingual Parents Talk to Children About Number in Mandarin and English - Chang, Alicia; Sandhofer, Catherine M. (Frontiers in Psychology, 2019)
Number-related language input has been shown to influence children’s number word acquisition and mathematical ability. Significant differences exist between how Mandarin Chinese speaking parents and monolingual English speaking parents use numeric language in speech to children, in particular Mandarin Chinese speaking parents use cardinal number much more frequently in speech to children than do English speaking parents. However, because previous studies have been conducted cross-nationally, research has been unable to disentangle the influences of language from culture. The current study examined numeric language input to preschool children with bilingual Mandarin-English American parents. Results show that when parents speak to their children in Mandarin Chinese, children hear more instances and examples of the cardinal number principle than when parents speak to their children in English. This suggests that differences between how the Mandarin and English languages are structured leads to disparities in how frequently children hear cardinal number in everyday speech.